Theoretical Investigation on the Reaction Pathways for Oxygen Reduction Reaction on Silicon Doped Graphene as Potential Metal-Free Catalyst. Issue 14 (28th October 2016) - Bai, Xiaowan; Zhao, Erjun; Li, Kai; Wang, Ying; Jiao, Menggai; He, Feng; Sun, Xiaoxu; Sun, He; Wu, Zhijian
Abstract : The reaction mechanism for oxygen reduction reaction (ORR) on Si-doped divacancy graphene is investigated by employing the density functional method. Our results show that all of the possible ORR elementary steps and charge transfer could take place within a small active region around the Si atom and its adjacent four carbon atoms. Among the possible reaction pathways, O2 dissociation and OOH hydrogenation into O + H2 O are the most favorable pathways kinetically. The rate-determining step is the O atom hydrogenation into OH with an energy barrier of 1.13 eV. This value is similar to 1.11 eV for the single layer SiC and 1.18 eV for SiC2 . Si-doped divacancy graphene has good tolerance against CO poisoning compared with Pt (111). Thus, Si-doped divacancy graphene could be a promising metal-free catalyst for ORR.